2014
DOI: 10.1074/jbc.r113.516716
|View full text |Cite
|
Sign up to set email alerts
|

Role of Stearoyl-CoA Desaturase-1 in Skin Integrity and Whole Body Energy Balance

Abstract: The skin is the single largest organ in humans, serving as a major barrier to infection, water loss, and abrasion. The functional diversity of skin requires the synthesis of large amounts of lipids, such as triglycerides, wax esters, squalene, ceramides, free cholesterol, free fatty acids, and cholesterol and retinyl esters. Some of these lipids are used as cell membrane components, signaling molecules, and a source of energy. An important class of lipid metabolism enzymes expressed in skin is the ⌬ 9 -desatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
62
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 64 publications
6
62
1
1
Order By: Relevance
“…Prior research has indicated that the two human SCD transcripts originate from one structural SCD gene via alternative polyadenylation sites [40]. The human SCD1 isoform, which is located on chromosome 10, is highly homologous (~85%) with murine Scd1 and is predominantly expressed in AT and liver [28]; however SCD1 expression has also been noted in skeletal muscle, heart, brain, lungs and pancreas [38,39,41]. In contrast to SCD1 expression, SCD5 is mostly confined to the pancreas and brain [37,42], yet low SCD5 expression has also been detected in the lungs, kidneys, heart and placenta [37,39,43].…”
Section: Scd Isoforms In Humans and Other Speciesmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior research has indicated that the two human SCD transcripts originate from one structural SCD gene via alternative polyadenylation sites [40]. The human SCD1 isoform, which is located on chromosome 10, is highly homologous (~85%) with murine Scd1 and is predominantly expressed in AT and liver [28]; however SCD1 expression has also been noted in skeletal muscle, heart, brain, lungs and pancreas [38,39,41]. In contrast to SCD1 expression, SCD5 is mostly confined to the pancreas and brain [37,42], yet low SCD5 expression has also been detected in the lungs, kidneys, heart and placenta [37,39,43].…”
Section: Scd Isoforms In Humans and Other Speciesmentioning
confidence: 99%
“…The human SCD1 isoform, which is located on chromosome 10, is highly homologous (~85%) with murine Scd1 and is predominantly expressed in AT and liver [28]; however SCD1 expression has also been noted in skeletal muscle, heart, brain, lungs and pancreas [38,39,41]. In contrast to SCD1 expression, SCD5 is mostly confined to the pancreas and brain [37,42], yet low SCD5 expression has also been detected in the lungs, kidneys, heart and placenta [37,39,43]. SCD5, which is unique to primate species, is located on chromosome 4 and its amino acid sequence is fairly dissimilar to any of the murine Scd isoforms [37,42].…”
Section: Scd Isoforms In Humans and Other Speciesmentioning
confidence: 99%
See 3 more Smart Citations